High Simulation Scenario Simulation Teaching of Acute and Critical Care Based on Wise Information Technology of Med - Wang, Chunmei (Journal of Mobile Multimedia, 2023)
Acute and critical care nursing is a subject with high requirements covering common emergency and critical care theories, common first aid, and clinical practice in various clinical departments. It involves theoretical knowledge of various specialties and a number of nursing operations. With the continuous updating of equipment and knowledge related to acute and critical care nursing, this discipline has also developed rapidly. However, due to the increasing shortage of medical teaching resources, it cannot effectively meet the teaching needs. In order to alleviate this clinical teaching pressure, this paper introduces the wise information technology of med, Sim Man 3G, a high-simulation simulator, into the teaching of acute and critical care nursing. Using Sim Man 3G can not only adjust the difficulty of treatment according to the needs of teaching, but also break through the clinical limitations, so the operation is very practical. The study found that the use of Sim Man 3G high simulation manikin in acute and critical care nursing could effectively improve the accuracy of case analysis and practical operation, which also improved the efficiency of teaching. In acute and critical care nursing, the highest teaching efficiency of Sim Man 3G was 96%, and the average teaching efficiency was 93.2%. The highest general teaching efficiency was 92%, and the average teaching efficiency was 88.6%. The teaching efficiency of the experimental group was 4.6% higher than that of the common group on average, and the overall quality was also improved. This showed that it is relatively successful to use Sim Man 3G high-fidelity simulator in acute and critical care nursing.